Penggunaan Media Quizizz dalam Meningkatkan Minat Belajar Siswa pada Materi Pembelajaran Ciri-Ciri Makhluk Hidup di Kelas 3 MI Salafiyah 1 Kauman - I’anatul Ashriyah; Umi Mahmudah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
The aim of this research is to determine the use of Quizizz media in increasing students' interest in learning about the characteristics of living things. This research method uses qualitative methods. The population and participants in this research were grade 3 students at MI Salafiyah 1 Kauman. The results of this research are concluded by an increase in students' interest in learning after using Quizizz as a learning medium. This can be seen from the results of questionnaires and interviews where students are happier and more enthusiastic about learning using Quizizz media. Based on the results of observations of student learning activities, there was an increase in learning, namely 75% and categorized as very good, while the results of student tests showed that out of 36 students, 32 students completed it. With these results, it can be shown that Quizizz media is indeed an effective medium for increasing students' interest in learning.